Perlindungan Hukum Terhadap Perjanjian Kerja Barista dengan Indische Coffee atas Keterlambatan Pembayaran Upah - Muhammad Sabir Rahman; Phireri Phireri; Yunisye Cenentya Wangka (Jurnal Litigasi Amsir, 2023)
This study aims to determine the legal protection of the barista work agreement with Indische Coffee for late payment of wages. The type of research used in this research is normative legal research. The research approach is a sociological juridical approach. The object of this research is located in Indische Coffee, the object studied is the barista work agreement with Indische Coffee for late payment of wages. The types and sources of data used in this study are primary data resulting from secondary research, namely legislation, institute decisions, published books and journals, tertiary data, namely data sources through articles and websites that are online. The results of the study show that the legal protection for workers who experience wage delays in indische coffee is regulated in the contents of the work agreement Article 1 Paragraph 2 Points b and Point d regulates wages and if there is a dispute, dispute resolution is regulated in Article 4.